Pengaruh Temperatur Karbonisasi terhadap Mikrostruktur dan Pembentukan Kristal pada Biokarbon Eceng Gondok sebagai Bahan Dasar Absorber Gelombang Elektromagnetik Radar - Imammuddin, Azam Muzakhim; Soeparman, Sudjito; Suprapto, Wahyono; Sonief, Achmad As'ad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Radar Absorbing Materials (RAM) or radar absorbing materials of radar electromagnetic waves are materials used to reduce or eliminate radiation of radar electromagnetic waves in order to avoid reflection of waves. At this time the development of RAM research leads to materials derived from nature. Some materials derived from nature that has been used as RAM such as rice husk, bamboo, coconut shell, coconut husk, wood fiber, and wood flour. In this study, eichornia crassipe is made into biocarbon or activated carbon for use as a base material for RAM. Carbonization is one way to transform water hyacinth into biocarbon or activated carbon. The method used in this research is Experimental Research. The independent variables of this research are carbonization temperature starting from temperature 500oC, 600oC, 700oC, 800oC, 900oC and 1000oC. The results showed that the higher the carbonization temperature, the more open pores will be with 2 Î¼m diameter at 1000oC, and the higher the carbonization temperature than the percentage of carbon crystal formed higher with the value of 14% at temperatures 900oC and 1000oC. The biocarbon structure of eichornia crassipe is crystalline and amorphous making it suitable for use as RAM material.